Resistance of rice genotypes to fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) - Silva,Cinthia Luzia Teixeira (2021)
ABSTRACT The fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), is an important rice pest which consumes leaf area during all phases of plant development. The objective of this study was to identify rice genotypes that provide antixenosis and antibiosis to fall armyworm. Antixenosis was investigated by measuring non-preference in free-choice and no-choice tests while antibiosis was determined by measuring biological parameters and nutritional indices of S. frugiperda in twelve rice genotypes. The genotype Miúdo Branco showed antixenosis to S. frugiperda, whereas the genotypes IR 64 and Bacaba Branco showed antibiosis to S. frugiperda by affecting insect development and prolonging insect life cycle. Insects that fed on Bacaba Branco genotype demonstrated the lowest nutritional indices. Since Miúdo Branco, IR 64 and Bacaba Branco showed moderate resistance, rice producers could use these genotypes as part of a control strategy for S. frugiperda.